Enemas with mesalazine increase the tissue contents of mucins in the colonic mucosa devoid of fecal stream - Martinez,Carlos Augusto Real (2019)
Abstract Purpose: To evaluate the inflammatory reaction and measure the content of mucins, in the colonic mucosa without fecal stream submit to intervention with mesalazine. Methods: Twenty-four rats were submitted to a left colostomy and a distal mucous fistula and divided into two groups according to euthanasia to be performed two or four weeks. Each group was divided into two subgroups according daily application of enemas containing saline or mesalazine at 1.0 g/kg/day. Colitis was diagnosed by histological analysis and the inflammatory reaction by validated score. Acidic mucins and neutral mucins were determined with the alcian-blue and periodic acid of Schiff techniques, respectively. Sulfomucin and sialomucin were identified by high iron diamine-alcian blue technique. The tissue contents of mucins were quantified by computer-assisted image analysis. Mann-Whitney test was used to analyze the results establishing the level of significance of 5%. Results: Enemas with mesalazine in colonic segments without fecal stream decreased the inflammation score and increased the tissue content of all subtypes of mucins. The increase of tissue content of neutral, acid and sulfomucin was related to the time of intervention. Conclusion: Mesalazine enemas reduce the inflammatory process and preserve the content of mucins in colonic mucosa devoid of fecal stream.